Answer Key to accompany Evergreen: A Guide to Writing and Evergreen with Readings: A Guide to Writing - Fawcett, Susan and Sandberg, Alvin (Boston Houghton Mifflin Company, 1996)
The answer key to all the exercises of the Evergreen with Readings textbook. Evergreen was designed for students who need to improve the writing skills so necessary to succeed in college and in most careers.
Keywords: Writing